2012
DOI: 10.1042/bst20120052
|View full text |Cite
|
Sign up to set email alerts
|

UPF1 involvement in nuclear functions

Abstract: UPF1 (up-frameshift 1) is a protein conserved in all eukaryotes that is necessary for NMD (nonsense-mediated mRNA decay). UPF1 mainly localizes to the cytoplasm and, via mechanisms that are linked to translation termination but not yet well understood, stimulates rapid destruction of mRNAs carrying a PTC (premature translation termination codon). However, some studies have indicated that in human cells UPF1 has additional roles, possibly unrelated to NMD, which are carried out in the nucleus. These might invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The affected animals had defects in multiple developmental processes, and it is currently unknown whether animal death resulted from a single or a combination of impaired processes. Moreover, in addition to their role in NMD, some NMD factors play a role in other cellular processes, including DNA synthesis, cell cycle progression, and the maintenance of telomeres (reviewed in [95,96]). Disruption of such NMD-unrelated processes could also contribute to animal lethality.…”
Section: The Lethality Of Severe Nmd Impairment In Plants Results Fromentioning
confidence: 99%
“…The affected animals had defects in multiple developmental processes, and it is currently unknown whether animal death resulted from a single or a combination of impaired processes. Moreover, in addition to their role in NMD, some NMD factors play a role in other cellular processes, including DNA synthesis, cell cycle progression, and the maintenance of telomeres (reviewed in [95,96]). Disruption of such NMD-unrelated processes could also contribute to animal lethality.…”
Section: The Lethality Of Severe Nmd Impairment In Plants Results Fromentioning
confidence: 99%
“…In this scenario, loss of NMD factors results in reduced transcription of these NMD targets, compensating for the concurrent increase in mRNA stability, which results in unchanged steady-state expression levels. A number of NMD factors are known to shuttle between the cytoplasm and the nucleus (Isken and Maquat 2008), and some are known to have nuclear functions (Brogna 1999; de Turris et al 2011; Varsally and Brogna 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Efficient depletion or elimination of several NMD components results in multisystemic developmental abnormalities and eventual embryonic lethality in worms, zebrafish, flies, and mice, which may be attributable to NMD or non-NMD functions (for review, see Hwang and Maquat 2011;Varsally and Brogna 2012). Notably, examination of available ChIP data revealed that 116 genes that were derepressed following NMD-inhibition have been previously identified as targets of the POU5F1 (also known as OCT4) TF, a master regulator of pluripotency (P < 0.005 by hypergeometric test) (Supplemental Table S3; Kim et al 2008).…”
Section: Role Of Nmd In the Mesc Transcriptional Programmentioning
confidence: 99%